Strategic Corporate Social Responsibility (SCSR): a systematic literature review - Athanasiadou, Chrisalena; Chatzoudes, Dimitrios; Theriou, Georgios (2020 Fourth World Conference on Smart Trends in Systems, Security and Sustainability (WorldS4), 2020)
Over the past few decades, Corporate Social Responsibility (CSR) has been perceived as an antecedent of competitive advantage. It was, moreover, placed at the top of the business agenda and recognized as a key driver of performance. Under this context, the present study sets to investigate how strategic CSR (SCSR) affects organizational performance and whether firms operating in “controversial” sectors should adopt SCSR activities. To this aim, this study reviews the body of knowledge on the topic, through a systematic review of the literature. After searching for academic publications in the Scopus database and selecting publications based on their relevance, 32 studies have been included in the review. Their analysis sheds light on common findings and contradicting arguments. Results show the main attributes of strategic, as opposed to non-strategic CSR activities. The importance of effective communication of SCSR activities is highlighted. SCSR is linked to “shared value”, as well as to competitive advantage, social innovation and good reputation. Voices of criticism focus on using SCSR as an empty promise that is used to counteract unethical behavior. Finally, more research is needed on the implementation of SCSR activities during recessionary periods.
Keywords: Co-création; Data collection; Innovation; Libre accès; Méthodes; Recherche; Relations industrielles

Strategic Corporate Social Responsibility (SCSR): a systematic literature review - Athanasiadou, Chrisalena; Chatzoudes, Dimitrios; Theriou, Georgios (2020 Fourth World Conference on Smart Trends in Systems, Security and Sustainability (WorldS4), 2020)
Over the past few decades, Corporate Social Responsibility (CSR) has been perceived as an antecedent of competitive advantage. It was, moreover, placed at the top of the business agenda and recognized as a key driver of performance. Under this context, the present study sets to investigate how strategic CSR (SCSR) affects organizational performance and whether firms operating in “controversial” sectors should adopt SCSR activities. To this aim, this study reviews the body of knowledge on the topic, through a systematic review of the literature. After searching for academic publications in the Scopus database and selecting publications based on their relevance, 32 studies have been included in the review. Their analysis sheds light on common findings and contradicting arguments. Results show the main attributes of strategic, as opposed to non-strategic CSR activities. The importance of effective communication of SCSR activities is highlighted. SCSR is linked to “shared value”, as well as to competitive advantage, social innovation and good reputation. Voices of criticism focus on using SCSR as an empty promise that is used to counteract unethical behavior. Finally, more research is needed on the implementation of SCSR activities during recessionary periods.
Keywords: Co-création; Data collection; Innovation; Libre accès; Méthodes; Recherche; Relations industrielles